#TITLE_ALTERNATIVE# - ZULFIKAR (NIM 12201034); Pembimbing : Leksono Mucharam, Dr., Ir., MAHATIR
One of the most EOR methods used to enhance oil recovery is surfactant injection. Surfactant is a surface active agent which could lower surface tension between oil and reservoir liquids, allowing easier spreading thus enhancing oil recovery. Theoritically, one of the most important factor that could effect the succesful of surfactant injection is the concentration itself. This paper investigates the effect of local surfactant concentration (four concentrations of anionic non-ionic blend surfactant with 63 percent solid active content) on oil recovery by imbibition experiment with soaking time varied from 4 hours up to 48 hours (2 days). The results of the experiments showed that there were significant incremental oil recovery in the range of 6 percent up to 15 percent of OOIP depends on surfactant concentration and soaking time of imbibition experiment. This preliminary study needs a further comprehensive investigation to determine the maximum of surfactant concentration and also the maximum of imbibition soaking time. Thus, an optimum oil recovery could be obtained from the most suitable local surfactant and also the best soaking time scheme. Keywords : Surfactant, Concentration, Soaking Time, Imbibition, Interfacial Tension.